Mediating role of depression in the association between alexithymia and nonsuicidal self-injury in a representative sample of adolescents in Taiwan - Wen-Ching Tang; Min-Pei Lin; Jo Yung-Wei Wu; Yueh-Ting Lee; Jianing You (BMC, 2022)
Abstract Background Nock's (2009) integrated theoretical model suggests that specific intrapersonal vulnerability factors caused by distal risk factors contribute to the development of nonsuicidal self-injury (NSSI). Alexithymia and depression have been found to predict NSSI. Based on Nock's model, alexithymia plays a distal risk factor role to increase the risk of depression-an intrapersonal vulnerability factor-and further increase the risk of NSSI. However, small or unrepresentative samples in past studies limit the generalizability of the results. This study examined the roles of depression and alexithymia in predicting NSSI, as well as the mediating effect of depression in the relation between alexithymia and NSSI in a large representative sample of adolescents in Taiwan. Methods Using a cross-sectional study design, a large representative sample of 2,170 senior high school students in Taiwan was assessed by self-report measures of alexithymia, depression, and NSSI. Mediation analyses were performed to examine whether the relation between alexithymia and NSSI was mediated by depression. The questionnaires were administered in classrooms. Results Results showed that alexithymia positively predicted NSSI (β = 0.23, p < .001) and depression can also positively predict NSSI (β = 0.41, p < .001). Additionally, the association between alexithymia and NSSI was fully mediated by depression. Conclusions This study data provided evidence for the mediating role of depression between alexithymia and NSSI, which can be explained by Nock's (2009) integrated theoretical model. The implications of the findings for future research and intervention were discussed.